Mechanical properties of titanium-based Ti–6Al–4V alloys manufactured by powder bed additive manufacture. Issue 2 (22nd January 2017) - Tong, J.; Bowen, C. R.; Persson, J.; Plummer, A.
Abstract : Additive manufacturing is currently a topic of considerable interest at both academic and industrial levels. While a significant amount of data exists on the mechanical properties and structure–property relationships of traditional wrought alloys, less information is available on alloys manufactured by additive manufacture. This review examines current state-of-the-art manufacture of titanium-based Ti–6Al–4V alloys by powder bed additive manufacture. Published mechanical properties to date are collected which include tensile strength, yield strength, hardness, wear, fracture toughness and fatigue. Differences in microstructure and properties compared to conventional wrought alloys of the same composition are described.